Pengaruh Model Pembelajaran Kooperatif Tipe Time Token Terhadap Hasil Belajar Siswa SMP - Rosalina Sisilia Santriana Son (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2019)
The low learning outcomes of students in integrated science subjects, particularly the material structure and function of plant organs, are due to the fact that the learning method used is still teacher-centered and the learning model is lack of innovation, leading to student inactivity, which leads to poor learning outcomes for students. The aim of this study was to determine the impact of the time token learning model on improving students' learning outcomes. The method used in this study is an experimental method using a research design called One Group Pretest-Postets Design, which uses one class as an experimental class with data collection techniques in the form of test questions. The data analysis used is a simple test of linear regression analysis. The results showed that using the time token learning model in learning had a positive impact on learning outcomes for Class VIII students at Siso State Middle School.